Nonaqueous electrolyte power storage element

JP2025003201APending Publication Date: 2025-01-09GS YUASA CORP

Patent Information

Application Number
JP2023103736
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-23
Publication Date
2025-01-09

AI Technical Summary

Benefits of technology

【0008】 本発明の一態様によれば、スピネル型結晶構造を有し、マンガン元素を含むリチウム遷移金属酸化物が正極に用いられた非水電解質蓄電素子であって、高温環境下で保存後の回復容量維持率が高い非水電解質蓄電素子を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025003201000001_ABST
    Figure 2025003201000001_ABST
Patent Text Reader

Abstract

To provide a nonaqueous electrolyte power storage element having a high recovery capacity retention rate after storage under a high-temperature environment.SOLUTION: The nonaqueous electrolyte power storage element according to one embodiment of the present invention includes: a positive electrode which contains a lithium transition metal oxide having a spinel type crystal structure and containing a manganese element; and a nonaqueous electrolyte. The lithium transition metal oxide is particles in which the ratio of an average particle diameter to an average primary particle diameter is 5 or less. The nonaqueous electrolyte contains at least one compound selected from the group consisting of a salt which has an anion having a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and containing no nitrogen element, a salt having an oxalate complex anion, an unsaturated cyclic carbonate, and a cyclic compound having a double bond between a sulfur atom and an oxygen atom.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-aqueous electrolyte electricity storage element. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. Non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring charge-transporting ions between the electrodes. As non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used.

[0003] LiMn 2 O 4 Lithium transition metal oxides having a spinel crystal structure and containing manganese element (hereinafter also referred to as "spinel-type lithium manganese oxides"), such as those represented by the following, are known. Spinel-type lithium manganese oxides have advantages such as that manganese element is abundant as a resource compared to cobalt element, nickel element, etc., can be obtained at low cost, and have excellent thermal stability. Patent Document 1 describes a nonaqueous electrolyte secondary battery having a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, and a nonaqueous electrolyte made of a nonaqueous solvent in which an electrolyte salt is dissolved, in which the positive electrode active material contains two types of spinel-type lithium manganate having different average particle sizes. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-9270 A Summary of the Invention [Problem to be solved by the invention]

[0005] It is desirable for a non-aqueous electrolyte storage element to maintain good performance even when stored in a high-temperature environment. However, when a non-aqueous electrolyte storage element using a spinel-type lithium manganese oxide for the positive electrode is stored in a high-temperature environment, the discharge capacity (recovery capacity) during subsequent charging and discharging is likely to decrease. In particular, when stored at a state of charge (SOC) of about 50%, the subsequent decrease in discharge capacity is significant.

[0006] An object of the present invention is to provide a nonaqueous electrolyte storage element in which a lithium transition metal oxide having a spinel crystal structure and containing manganese is used for a positive electrode, the nonaqueous electrolyte storage element having a high recovery capacity retention rate after storage in a high-temperature environment. [Means for solving the problem]

[0007] A nonaqueous electrolyte storage element according to one embodiment of the present invention comprises a positive electrode having a spinel crystal structure and containing a lithium transition metal oxide containing elemental manganese, and a nonaqueous electrolyte, wherein the lithium transition metal oxide is in the form of particles having a ratio of an average particle size to an average primary particle size of 5 or less, and the nonaqueous electrolyte contains at least one compound selected from the group consisting of a salt having an anion having a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and not containing a nitrogen element, a salt having an oxalate complex anion, an unsaturated cyclic carbonate, and a cyclic compound having a double bond between a sulfur atom and an oxygen atom. Effect of the Invention

[0008] According to one aspect of the present invention, it is possible to provide a nonaqueous electrolyte storage element in which a lithium transition metal oxide having a spinel crystal structure and containing manganese is used for a positive electrode, the nonaqueous electrolyte storage element having a high recovery capacity retention rate after storage in a high-temperature environment. [Brief description of the drawings]

[0009] [Figure 1]FIG. 1 is a perspective view showing one embodiment of a nonaqueous electrolyte electricity storage element. [Diagram 2] FIG. 2 is a schematic diagram showing one embodiment of an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] First, an overview of the nonaqueous electrolyte electricity storage element disclosed in this specification will be described.

[0011] [1] A nonaqueous electrolyte storage element according to one embodiment of the present invention comprises a positive electrode having a spinel crystal structure and containing a lithium transition metal oxide containing elemental manganese, and a nonaqueous electrolyte, wherein the lithium transition metal oxide is in the form of particles having a ratio of an average particle size to an average primary particle size of 5 or less, and the nonaqueous electrolyte contains at least one compound selected from the group consisting of a salt having an anion having a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and not containing a nitrogen element, a salt having an oxalate complex anion, an unsaturated cyclic carbonate, and a cyclic compound having a double bond between a sulfur atom and an oxygen atom.

[0012] The nonaqueous electrolyte storage element described in [1] above is a nonaqueous electrolyte storage element in which a lithium transition metal oxide having a spinel crystal structure and containing manganese element, i.e., a spinel-type lithium manganese oxide, is used for the positive electrode, and has a high recovery capacity retention rate after storage in a high-temperature environment. The reason why such an effect occurs is unclear, but the following reason is presumed. The reason why the recovery capacity retention rate after storage in a high-temperature environment in a conventional nonaqueous electrolyte storage element in which a spinel-type lithium manganese oxide is used for the positive electrode is low is that the manganese element in the spinel-type lithium manganese oxide dissolves into the nonaqueous electrolyte during storage in a high-temperature environment. Therefore, by making the nonaqueous electrolyte contain at least one compound (hereinafter also referred to as "compound X") selected from the group consisting of a salt having an anion having a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and not containing a nitrogen element, a salt having an oxalate complex anion, an unsaturated cyclic carbonate, and a cyclic compound having a double bond between a sulfur atom and an oxygen atom, a coating derived from compound X is formed on the particle surface of the spinel-type lithium manganese oxide, and the dissolution of the manganese element is suppressed. Furthermore, when the spinel-type lithium manganese oxide is a particle having a ratio of the average particle size to the average primary particle size of 5 or less (hereinafter also referred to as "monoparticle particles"), an increase in surface area due to particle cracking between primary particles caused by charging and discharging, etc., is unlikely to occur. Therefore, a state in which a highly uniform and sufficiently thick coating is formed on the surface of the monoparticle particles is easily maintained, and the elution of manganese element is further suppressed. For these reasons, it is presumed that the nonaqueous electrolyte storage element described in the above [1] has a high recovery capacity retention rate after storage in a high-temperature environment.

[0013] For example, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O 2 etc., α-NaFeO 2The inventors have found that in the case of a conventional non-aqueous electrolyte storage element in which a lithium transition metal oxide containing manganese is used for the positive electrode, the manganese element is unlikely to dissolve even when stored in a high temperature environment. This is because, for example, when stored in a charged state of about SOC 50%, the manganese element in the spinel-type lithium manganese oxide is present as a trivalent manganese element, whereas the manganese element in the α-NaFeO 2 This is believed to be due to the fact that the manganese element in the spinel-type lithium transition metal oxide exists in a tetravalent state. It is generally known that trivalent manganese element is easily changed in valence to divalent manganese element and tetravalent manganese element by a disproportionation reaction, and divalent manganese element has high solubility in nonaqueous electrolytes. Therefore, the nonaqueous electrolyte storage element described in [1] above can be said to solve the problem specific to conventional nonaqueous electrolyte storage elements in which a spinel-type lithium manganese oxide is used in the positive electrode, that is, the recovery capacity retention rate decreases due to the elution of manganese element when stored in a high-temperature environment.

[0014] The "average primary particle diameter" of the spinel-type lithium manganese oxide is the average value of the primary particle diameters of any 50 primary particles constituting the spinel-type lithium manganese oxide observed under a scanning electron microscope (SEM). A primary particle is a particle in which no grain boundary is observed in appearance under the above SEM observation. The primary particle diameter of the primary particles is determined as follows. The shortest diameter passing through the center of the minimum circumscribing circle of the primary particle is defined as the short diameter, and the diameter passing through the center and perpendicular to the short diameter is defined as the long diameter. The average value of the long diameter and the short diameter is defined as the particle diameter. When there are two or more shortest diameters, the longest diameter perpendicular to the short diameter is defined as the short diameter. Specifically, the primary particle diameter of the primary particles based on the SEM observation is determined as follows. (1) Preparation of the measurement sample The positive electrode to be measured is fixed with a thermosetting resin. The cross section of the positive electrode fixed with the resin is exposed by ion milling to prepare a measurement sample. (2) Acquiring SEM images To obtain SEM images, a JSM-7001F (manufactured by JEOL Ltd.) scanning electron microscope is used. SEM images are obtained by observing secondary electron images. The acceleration voltage is 5 kV. The observation magnification is set so that the number of particles appearing in one field of view is between 3 and 15 (in the case of secondary particles formed by agglomeration of multiple primary particles, the secondary particles are used). The obtained SEM image is saved as an image file. Other conditions such as spot diameter, working distance, irradiation current, brightness, and focus are appropriately set so that the outlines of the particles are clearly visible. (3) Calculation of primary particle size for primary particles Randomly extract 50 primary particles from the obtained SEM image, and measure the primary particle diameter of each of them using the method described above. Calculate the average value of each primary particle diameter of the primary particles, and use this as the "average primary particle diameter" of the primary particles.

[0015] The "average particle size" of spinel-type lithium manganese oxide is the value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% (D50: median diameter) based on the particle size distribution measured by the laser diffraction / scattering method for a diluted solution of spinel-type lithium manganese oxide diluted with a solvent in accordance with JIS-Z-8815 (2013). It has been confirmed that the average particle size based on the above measurement is almost identical to the average particle size, which is the average value of the particle size (secondary particle diameter in the case of secondary particles) of 50 particles extracted from the SEM image of the particles, excluding extremely large and extremely small particles. The particle size of each particle based on the measurement from this SEM image is calculated as follows. The SEM image is obtained in accordance with the case of calculating the "average primary particle size" described above. The shortest diameter passing through the center of the minimum circumscribing circle of each particle is the minor diameter, and the diameter passing through the center and perpendicular to the minor diameter is the major diameter. The particle diameter of each particle is the average of the major axis and the minor axis. When there are two or more shortest diameters, the diameter that intersects at right angles is the longest diameter.

[0016] The spinel-type lithium manganese oxide for which the average primary particle size and average particle size are measured is the spinel-type lithium manganese oxide before charging and discharging or when fully discharged by the following method. First, the nonaqueous electrolyte storage element is charged at a constant current of 0.05 C until it reaches the charge end voltage in normal use, and is fully charged. After a 30-minute rest, it is discharged at a constant current of 0.05 C until it reaches the lower limit voltage in normal use. The element is disassembled, the positive electrode is removed, and a half cell is assembled with a metallic lithium electrode as the counter electrode. The positive electrode potential is then measured at a current of 10 mA per 1 g of positive electrode active material until the positive electrode potential reaches 3.5 V vs. Li / Li. + The positive electrode is adjusted to a fully discharged state by constant current discharge until the positive electrode reaches a fully discharged state. The positive electrode is disassembled again and the positive electrode is taken out. The non-aqueous electrolyte attached to the taken positive electrode is thoroughly washed using dimethyl carbonate and dried at room temperature for a day and night. The dried positive electrode is subjected to measurement of the average primary particle size. Furthermore, spinel-type lithium manganese oxide is extracted from the dried positive electrode. The extracted spinel-type lithium manganese oxide is subjected to measurement of the average particle size. The operations from disassembling the non-aqueous electrolyte storage element to extracting the positive electrode and spinel-type lithium manganese oxide are performed in an argon atmosphere with a dew point of -60°C or less. Here, normal use refers to the case where the non-aqueous electrolyte storage element is used by adopting the charge and discharge conditions recommended or specified for the non-aqueous electrolyte storage element. The current at which the rated capacity of the non-aqueous electrolyte storage element is discharged in one hour is defined as 1C.

[0017] [2] In the nonaqueous electrolyte storage element according to the above [1], the compound may be at least one selected from the group consisting of lithium difluorophosphate, lithium bis(oxalato)borate, vinylene carbonate, and 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane).

[0018] The nonaqueous electrolyte electricity storage element described in [2] above has a higher recovery capacity retention rate after storage in a high-temperature environment.

[0019] [3] In the nonaqueous electrolyte storage element according to the above [1] or [2], the content of the compound in the nonaqueous electrolyte may be 0.1% by mass or more and 10% by mass or less.

[0020] The nonaqueous electrolyte electricity storage element described in [3] above has a higher recovery capacity retention rate after storage in a high-temperature environment.

[0021] When the compound X contained in the non-aqueous electrolyte is a non-ionic compound (unsaturated cyclic carbonates such as vinylene carbonate and 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane, and cyclic compounds having a double bond between a sulfur atom and an oxygen atom), the type and content of the compound X are identified by liquid chromatography-mass spectrometry (LC-MS) and gas chromatography-mass spectrometry (GC-MS). Specifically, the method is as follows. The LC-MS and GC-MS measurements are performed successively under the same conditions. (A1) Collection of non-aqueous electrolyte First, the nonaqueous electrolyte storage element is disassembled to remove the nonaqueous electrolyte. If the nonaqueous electrolyte cannot be removed, the nonaqueous electrolyte storage element is centrifuged to remove the nonaqueous electrolyte. If the nonaqueous electrolyte cannot be removed even after centrifugation, an appropriate extraction solvent (e.g., acetonitrile) is injected into the nonaqueous electrolyte storage element, and the nonaqueous electrolyte diluted with the extraction solvent is removed. (A2)LC-MS The components of the collected non-aqueous electrolyte are analyzed by LC-MS. The LC-MS analysis is performed in the following order of qualitative analysis and quantitative analysis. The LC-MS analysis is performed using Waters' "Acquity H" and "Xevo G2-5QTof" instruments. Water is used as the eluent. (qualitative analysis) The measurement sample (non-aqueous electrolyte) is subjected to LC-MS analysis. If the peaks in the obtained liquid chromatogram cannot be separated, a GC-MS analysis, described below, is performed instead of the LC-MS analysis. If the peaks can be separated, the components contained in the measurement sample are predicted from the MS spectrum of each peak. A known sample of the predicted components (hereinafter referred to as "predicted components") is subjected to LC-MS analysis. The retention times and MS spectrum of the peaks corresponding to each predicted component of the measurement sample are compared with the retention times and MS spectrum of the peaks of a known sample of each predicted component, and if they match, the prediction is presumed to be correct. (Quantitative analysis) Quantitative analysis is performed using the calibration curve method. First, a known sample of the predicted component with a known concentration is measured by LC-MS, and a calibration curve is created by calculating the peak area. The calibration curve is calculated using the coefficient of determination (r 2 ) is created so that it is between 0.999 and 1. The content of the predicted component in the measurement sample is calculated from the calibration curve and the peak area of ​​the predicted component in the measurement sample. (A3)GC-MS The GC-MS analysis is carried out in the following order: qualitative analysis and quantitative analysis. The GC-MS analysis equipment used is the Agilent 5975C. Argon is used as the carrier gas. (qualitative analysis) A measurement sample (non-aqueous electrolyte) is subjected to GC-MS analysis. The components contained in the sample are predicted from the MS spectrum of each peak in the obtained gas chromatogram. A known sample of the predicted components is subjected to GC-MS analysis. The retention time and MS spectrum of the peak corresponding to the predicted component of the measurement sample are compared with the retention time and MS spectrum of the peak of a known sample of each predicted component, and if they match, the above prediction is presumed to be correct. (Quantitative analysis) The quantitative analysis is performed by the calibration curve method. The quantitative analysis by GC-MS is performed in the same manner as the quantitative analysis by LC-MS described above, and the content of each predicted component is determined.

[0022] When the compound X contained in the non-aqueous electrolyte is an ionic compound (a salt having an anion containing a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and not containing a nitrogen element, such as lithium difluorophosphate and lithium bis(oxalato)borate, and a salt having an oxalato complex anion), the type and content of the compound X are identified by ion chromatography (IC). Water is used as the eluent. Specifically, the measurement is carried out as follows. The IC measurements are carried out continuously under the same conditions. (B1) Collection of non-aqueous electrolyte The non-aqueous electrolyte is extracted in the same manner as in "(A1) Collection of non-aqueous electrolyte" above. (B2)IC analysis The components of the collected non-aqueous electrolyte are analyzed by IC. The IC analysis is performed in the following order: qualitative analysis and quantitative analysis. (qualitative analysis) A measurement sample (non-aqueous electrolyte) is subjected to IC analysis. The components contained in the measurement sample are predicted from the peak positions of each peak in the obtained ion chromatogram. A known sample of the predicted components (hereinafter referred to as "predicted components") is subjected to IC analysis. The retention times of the peaks corresponding to each predicted component in the measurement sample are compared with the retention times of the peaks of known samples of each predicted component, and if they match, the prediction is presumed to be correct. (Quantitative analysis) Quantitative analysis is performed using the calibration curve method. Quantitative analysis by IC is performed in the same manner as the quantitative analysis by LC-MS described above, and the content of each predicted component is determined.

[0023] A nonaqueous electrolyte electricity storage element, an electricity storage device, a method for manufacturing a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention, and other embodiments will be described in detail. Note that the names of the components (elementary components) used in each embodiment may differ from the names of the components (elementary components) used in the background art.

[0024] <Non-aqueous electrolyte electricity storage element> A nonaqueous electrolyte storage element (hereinafter, also simply referred to as "storage element") according to one embodiment of the present invention includes an electrode assembly having a positive electrode, a negative electrode, and a separator, a nonaqueous electrolyte, and a container that contains the electrode assembly and the nonaqueous electrolyte. The electrode assembly is usually a laminated type in which a plurality of positive electrodes and a plurality of negative electrodes are laminated with a separator interposed therebetween, or a wound type in which a positive electrode and a negative electrode are laminated with a separator interposed therebetween and wound. At least a part of the nonaqueous electrolyte exists in a state in which it is impregnated into the positive electrode, the negative electrode, and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter, also simply referred to as "secondary battery") will be described.

[0025] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.

[0026] The positive electrode substrate is conductive. Whether or not it has "conductivity" is determined by whether the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 -2 The threshold value is Ω·cm. The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferred from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, etc., and a foil is preferred from the viewpoint of cost. Therefore, aluminum foil or an aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or an aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H-4160 (2006).

[0027] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.

[0028] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.

[0029] The positive electrode active material layer contains a spinel-type lithium manganese oxide, i.e., a lithium transition metal oxide having a spinel crystal structure and containing manganese element. The spinel-type lithium manganese oxide is a component that functions as a positive electrode active material. The positive electrode active material layer contains optional components such as other positive electrode active materials other than the spinel-type lithium manganese oxide, conductive agents, binders, thickeners, and fillers as necessary.

[0030] The spinel type lithium manganese oxide contains lithium, manganese and oxygen, and may further contain one or more other elements. Examples of other elements include nickel, titanium, vanadium, chromium, iron, copper, zinc, boron, phosphorus, magnesium, aluminum, calcium, zirconium, molybdenum, tungsten, and halogen elements. The total content ratio of lithium, manganese and oxygen in the total constituent elements of the spinel type lithium manganese oxide may be 80 mol% or more, 90 mol% or more, or 99 mol% or more. The composition ratio of the spinel type lithium manganese oxide (content ratio of each element) refers to the composition ratio before charging and discharging or when fully discharged by the above method.

[0031] As the spinel-type lithium manganese oxide, for example, a compound represented by the following formula (1) can be used. Li 1+α Mn 2-α-β A β O 4 (1) In formula (1), A is at least one selected from the group consisting of Ni, Ti, V, Cr, Fe, Cu, Zn, B, P, Mg, Al, Ca, Zr, Mo, and W. α and β satisfy 0≦α≦0.3 and 0≦β≦0.5, respectively.

[0032] In formula (1), α may be 0.1 or more and 0.25 or less. β may be 0 or more and 0.1 or less, or 0 or more and 0.05 or less. The spinel type lithium manganese oxide is, for example, LiMn 2 O 4、 LiNi 0.5 Mn 1.5 O 4 can be used.

[0033] The spinel-type lithium manganese oxide is a single particle system particle having a ratio of the average particle diameter to the average primary particle diameter of 5 or less. The ratio of the average particle diameter to the average primary particle diameter of the spinel-type lithium manganese oxide is preferably 4 or less, more preferably 3.5 or less, and may be 3 or less. By having the ratio of the average particle diameter to the average primary particle diameter be equal to or less than the above upper limit, the recovery capacity maintenance rate after storage in a high temperature environment can be further increased. The lower limit of the ratio of the average particle diameter to the average primary particle diameter of the spinel-type lithium manganese oxide may be 1 or 2. In addition, due to the difference between the measurement method of the average primary particle diameter and the measurement method of the average particle diameter, the lower limit of the ratio of the average particle diameter to the average primary particle diameter may be less than 1, for example, 0.9. The ratio of the average particle diameter to the average primary particle diameter of the spinel-type lithium manganese oxide may be equal to or more than any of the above lower limits and equal to or less than any of the above upper limits.

[0034] The spinel-type lithium manganese oxide, which is a single-particle particle, may be a particle made of primary particles (single particle), a secondary particle formed by agglomeration of multiple primary particles, or a mixed particle of a single particle and a secondary particle, so long as the ratio of the average particle size to the average primary particle size is 5 or less.

[0035] The spinel-type lithium manganese oxide, which is a single-particle particle, can be produced by a known method, and a commercially available product may be used. In the production process of the spinel-type lithium manganese oxide, the single-particle particle can be obtained by increasing the primary particle diameter by growing the crystals of multiple primary particles, for example, by increasing the firing temperature or the firing time. Alternatively, the single-particle particle can be obtained by crushing the secondary particles.

[0036] The average particle size of the spinel-type lithium manganese oxide is preferably, for example, 0.1 μm or more and 20 μm or less. The lower limit of the average particle size is more preferably 1 μm, and further preferably 3 μm, 5 μm, or 7 μm. By setting the average particle size of the spinel-type lithium manganese oxide to the lower limit or more, the production or handling of the spinel-type lithium manganese oxide becomes easy. By setting the average particle size of the spinel-type lithium manganese oxide to the upper limit or less, the electronic conductivity of the positive electrode active material layer is improved.

[0037] In order to obtain a spinel-type lithium manganese oxide with a predetermined average particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. When pulverizing, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, a wind classifier, etc. are used as necessary for both dry and wet methods.

[0038] The content of the spinel-type lithium manganese oxide in the positive electrode active material layer is preferably 50% by mass or more and 99% by mass or less, more preferably 70% by mass or more and 98% by mass or less, even more preferably 80% by mass or more and 97% by mass or less, and even more preferably 90% by mass or more or 94% by mass or more. By setting the content of the spinel-type lithium manganese oxide in the above range, it is possible to achieve both high energy density and manufacturability of the positive electrode active material layer.

[0039] The positive electrode active material layer may contain a positive electrode active material other than the spinel-type lithium manganese oxide, but the content of the spinel-type lithium manganese oxide in the total positive electrode active material contained in the positive electrode active material layer is preferably 80% by mass or more and 100% by mass or less, more preferably 95% by mass or more and 100% by mass or less, and even more preferably 100% by mass.

[0040] The content of all the positive electrode active materials in the positive electrode active material layer is preferably 50% by mass or more and 99% by mass or less, more preferably 70% by mass or more and 98% by mass or less, even more preferably 80% by mass or more and 97% by mass or less, and even more preferably 90% by mass or more or 94% by mass or more. By setting the content of the positive electrode active materials in the above range, it is possible to achieve both high energy density and manufacturability of the positive electrode active material layer.

[0041] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. These materials may also be used in combination. For example, a material in which carbon black and CNT are combined may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them.

[0042] The content of the conductive agent in the positive electrode active material layer is preferably from 1 mass % to 10 mass %, more preferably from 3 mass % to 9 mass %. By setting the content of the conductive agent in the above range, the energy density of the nonaqueous electrolyte storage element can be increased.

[0043] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0044] The content of the binder in the positive electrode active material layer is preferably 0.5% by mass to 10% by mass, more preferably 1% by mass to 5% by mass. The upper limit of the binder content may be 3% by mass or 2% by mass. By setting the binder content within the above range, the spinel-type lithium manganese oxide, etc. can be stably maintained.

[0045] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be deactivated in advance by methylation or the like. When a thickener is used in the positive electrode active material layer, the content of the thickener in the positive electrode active material layer can be 0.1% by mass or more and 8% by mass or less, and is usually preferably 5% by mass or less, and more preferably 2% by mass or less. The technology disclosed herein can be preferably implemented in an embodiment in which the positive electrode active material layer does not contain a thickener.

[0046] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. When a filler is used in the positive electrode active material layer, the content of the filler in the positive electrode active material layer can be 0.1% by mass or more and 8% by mass or less, and is usually preferably 5% by mass or less, and more preferably 2% by mass or less. The technology disclosed herein can be preferably implemented in an embodiment in which the positive electrode active material layer does not contain a filler.

[0047] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as materials other than the spinel-type lithium manganese oxide, other positive electrode active materials, conductive agents, binders, thickeners, and fillers.

[0048] (Negative electrode) The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode.

[0049] The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, nickel-plated steel, and aluminum, or alloys thereof, carbonaceous materials, etc. are used as the material of the negative electrode substrate. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate include foils, vapor deposition films, meshes, and porous materials, and foils are preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0050] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.

[0051] The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer contains optional components such as a conductive agent, a binder, a thickener, a filler, etc., as necessary. The optional components such as a conductive agent, a binder, a thickener, a filler, etc. can be selected from the materials exemplified for the positive electrode above.

[0052] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as materials other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0053] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for lithium ion secondary batteries. Examples of the negative electrode active material include metallic lithium; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li 4 Ti 5 O 12 , LiTiO 2、TiNb 2 O 7 Examples of the material include titanium-containing oxides such as titanium oxide, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitized carbon or non-graphitizable carbon). Among these materials, graphite and non-graphitic carbon are preferred. In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.

[0054] "Graphite" refers to graphite that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of availability of materials with stable physical properties.

[0055] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.

[0056] Here, the "discharged state" of the carbon material means a state in which the carbon material, which is the negative electrode active material, is discharged so that lithium ions that can be absorbed and released during charging and discharging are sufficiently released from the carbon material, which is the negative electrode active material. For example, in a half cell using a negative electrode containing a carbon material as the negative electrode active material as a working electrode and metallic lithium as a counter electrode, the open circuit voltage is 0.7 V or more.

[0057] "Non-graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.

[0058] "Graphitizable carbon" means the above d 002This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.

[0059] The negative electrode active material is usually a particle (powder). The average particle size of the negative electrode active material can be, for example, 1 nm or more and 100 μm or less. When the negative electrode active material is a carbon material, a titanium-containing oxide, or a polyphosphate compound, the average particle size may be 1 μm or more and 100 μm or less. When the negative electrode active material is Si, Sn, Si oxide, Sn oxide, or the like, the average particle size may be 1 nm or more and 1 μm or less. By setting the average particle size of the negative electrode active material to the above lower limit or more, the negative electrode active material can be easily manufactured or handled. By setting the average particle size of the negative electrode active material to the above upper limit or less, the electronic conductivity of the negative electrode active material layer is improved. In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, or the like is used. The pulverization method and the classification method can be selected from, for example, the methods exemplified for the positive electrode. When the negative electrode active material is a metal such as metallic lithium, the negative electrode active material layer may be in the form of a foil.

[0060] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% by mass to 99% by mass, more preferably 90% by mass to 98% by mass. By setting the content of the negative electrode active material in the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.

[0061] When a conductive agent is used in the negative electrode active material layer, the content of the conductive agent in the negative electrode active material layer may be 1 mass % or more and 10 mass % or less, or may be 3 mass % or more and 9 mass % or less. When the negative electrode active material is a carbon material or the like, the negative electrode active material layer does not need to contain a conductive agent.

[0062] The binder content in the negative electrode active material layer is preferably 1% by mass to 10% by mass, more preferably 3% by mass to 9% by mass. By setting the binder content in the above range, the negative electrode active material can be stably held.

[0063] The content of the thickener in the negative electrode active material layer is preferably from 0.1% by mass to 8% by mass, and more preferably from 0.3% by mass to 5% by mass.

[0064] When a filler is used in the negative electrode active material layer, the content of the filler in the negative electrode active material layer can be 0.1 mass% or more and 8 mass% or less, and usually, 5 mass% or less is preferable, and 2 mass% or less is more preferable. The technology disclosed herein can be preferably implemented in an embodiment in which the negative electrode active material layer does not contain a filler.

[0065] (Separator) The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of non-aqueous electrolyte retention. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.

[0066] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C under an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C. Examples of materials with a mass loss of a predetermined amount or less include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the energy storage element.

[0067] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.

[0068] As the separator, a polymer gel composed of a polymer and a non-aqueous electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of the polymer gel has an effect of suppressing leakage. As the separator, the above-mentioned porous resin film or nonwoven fabric may be used in combination with the polymer gel.

[0069] (Non-aqueous electrolyte) The non-aqueous electrolyte contains at least one compound X selected from the group consisting of a salt having an anion having a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and not containing a nitrogen atom, a salt having an oxalato complex anion, an unsaturated cyclic carbonate, and a cyclic compound having a double bond between a sulfur atom and an oxygen atom. One or more compounds X can be used. For example, as the compound X, a salt having an anion having a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and not containing a nitrogen atom, an unsaturated cyclic carbonate, and a cyclic compound having a double bond between a sulfur atom and an oxygen atom can be used in combination.

[0070] Examples of salts having an anion that has a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and does not contain a nitrogen element include lithium salts, sodium salts, potassium salts, magnesium salts, and onium salts, with lithium salts being preferred.

[0071] An anion that has a double bond between a sulfur atom and an oxygen atom and does not contain a nitrogen element is the fluorosulfonate anion (SO 3 F - ), trifluoromethanesulfonate anion (SO 3 CF 3 - ) and the like. An anion having a double bond between a phosphorus atom and an oxygen atom and not containing a nitrogen element is a difluorophosphate anion (PO 2 F 2 - ), monofluorophosphate anion (PO 3 F 2- The anion having a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and not containing a nitrogen element preferably contains a fluorine element. The anion having a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and not containing a nitrogen element is preferably an inorganic anion.

[0072] As an example of a salt having a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and an anion that does not contain a nitrogen element, lithium trifluoromethanesulfonate (LiSO 3 CF 3), lithium difluorophosphate (LiPO 2 F 2 ), lithium monofluorophosphate (Li 2 PO 3 F), and the like, with lithium difluorophosphate being preferred. One or more types of salts having a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and an anion not containing a nitrogen element can be used.

[0073] Examples of salts having an oxalato complex anion include lithium salts, sodium salts, potassium salts, magnesium salts, and onium salts, with lithium salts being preferred.

[0074] The oxalato complex anion is difluorooxalatoborate anion (BF 2 (C 2 O 4 ) - ), bis(oxalato)borate anion (B(C 2 O 4 ) 2 - ), difluorobis(oxalate)phosphate anion (PF 2 (C 2 O 4 ) 2 - ), tetrafluorooxalate phosphate anion (PF 4 (C 2 O 4 ) - ), tris(oxalate)phosphate anion (P(C 2 O 4 ) 3 - The oxalato complex anion preferably contains a boron element.

[0075] Examples of salts having an oxalato complex anion include lithium difluorooxalatoborate (LiBF 2 (C 2 O 4 )), lithium bis(oxalato)borate (LiB(C 2 O 4 )2 ), lithium difluorobis(oxalate)phosphate (LiPF 2 (C 2 O 4 ) 2 ), lithium tetrafluorooxalate phosphate (LiPF 4 (C 2 O 4 )), lithium tris(oxalato)phosphate (LiP(C 2 O 4 ) 3 Of these, lithium difluorooxalatoborate and lithium bis(oxalato)borate are preferred, and lithium bis(oxalato)borate is more preferred. One or more types of salts having an oxalato complex anion can be used.

[0076] Examples of the unsaturated cyclic carbonate include vinylene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, vinylethylene carbonate, methylvinylene carbonate, and ethylvinylene carbonate. The unsaturated cyclic carbonate is preferably one having a carbon-carbon unsaturated bond in the ring structure, and more preferably vinylene carbonate. The unsaturated cyclic carbonate can be used alone or in combination of two or more.

[0077] The cyclic compound having a double bond between a sulfur atom and an oxygen atom is usually an organic compound. The cyclic compound is preferably a compound having a heterocyclic structure containing a sulfur element. Examples of the cyclic compound include compounds having a cyclic sulfate structure, a cyclic sulfonate structure, a cyclic sulfone structure, a cyclic sulfite structure, and a cyclic sulfoxide structure.

[0078] A compound with a cyclic sulfate structure is one in which each of the two carbon atoms is an oxysulfonyloxy group (-OS(=O) 2-O-) is a compound containing a ring structure. Specific examples of compounds having a cyclic sulfate structure include ethylene sulfate, 1,3-propylene sulfate, 2,3-propylene sulfate, 4,5-pentene sulfate, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, etc.

[0079] A compound with a cyclic sulfonate structure is one in which each of the two carbon atoms is a sulfonyloxy group (-S(=O) 2 O-) is a compound containing a ring structure bonded to the cyclic sulfonate structure. The compound having a cyclic sulfonate structure may be a cyclic sulfonate ester or a sultone. Specific examples of the compound having a cyclic sulfonate structure (cyclic sulfonate ester) include 1,3-propane sultone, 1,4-butane sultone, 1,3-propene sultone, 1-methyl-1,3-propene sultone, 2-methyl-1,3-propene sultone, 3-methyl-1,3-propene sultone, and 1,4-butene sultone.

[0080] A compound with a cyclic sulfone structure is one in which each of the two carbon atoms is a sulfonyl group (-S(=O) 2 -) is a compound containing a ring structure bonded to the cyclic sulfone structure. Specific examples of compounds having a cyclic sulfone structure include sulfolane, 3-methylsulfolane, 3-sulfolene, 1,1-dioxothiophene, 3-methyl-2,5-dihydrothiophene-1,1-dioxide, and methyl 3-sulfolene-3-carboxylate.

[0081] A compound having a cyclic sulfite structure refers to a compound containing a ring structure in which two carbon atoms are each bonded to an oxysulfinyloxy group (-OS(=O)-O-). Specific examples of compounds having a cyclic sulfite structure include ethylene sulfite, 1,2-propylene glycol sulfite, trimethylene sulfite, and 1,3-butylene glycol sulfite.

[0082] A compound having a cyclic sulfoxide structure refers to a compound containing a ring structure in which two carbon atoms are each bonded to a sulfinyl group (-S(=O)-). A specific example of a compound having a cyclic sulfoxide structure is tetramethylene sulfoxide.

[0083] Examples of cyclic compounds having a double bond between a sulfur atom and an oxygen atom include sulfonyl groups (-S(=O) 2 -) is preferred. Examples of such compounds include the above-mentioned compounds having a cyclic sulfate structure, a cyclic sulfonate structure, a cyclic sulfone structure, and the like. Among these, compounds having a cyclic sulfate structure are preferred, and 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane) is more preferred. One or more types of cyclic compounds having a double bond between a sulfur atom and an oxygen atom can be used.

[0084] Among these, at least one selected from the group consisting of lithium difluorophosphate, lithium bis(oxalate)borate, vinylene carbonate, and 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane) is preferred as the compound X. By using these compounds as the compound X, the recovery capacity retention rate after storage in a high-temperature environment can be further increased.

[0085] The content of compound X in the non-aqueous electrolyte is preferably 0.1% by mass or more and 10% by mass or less. When the content of compound X in the non-aqueous electrolyte is within the above range, a moderate amount of coating is formed on the surface of the single particle particles that are spinel-type lithium manganese oxide, and the recovered capacity retention rate after storage in a high-temperature environment can be further increased. The lower limit of the content of compound X may be 0.2% by mass, 0.3% by mass, 0.5% by mass, 1% by mass, or 2% by mass. The upper limit of the content of compound X may be 5% by mass, 3% by mass, 2% by mass, or 1% by mass. The content of compound X may be within a range that combines any of the above lower limits and any of the above upper limits.

[0086] The non-aqueous electrolyte is usually a non-aqueous electrolyte. The non-aqueous electrolyte contains a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous electrolyte contains the above-mentioned compound X. When the compound X is at least one of a salt having an anion having a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and not containing a nitrogen element, and a salt having an oxalato complex anion, the non-aqueous electrolyte may contain these compounds as electrolyte salts, or may contain electrolyte salts separately from these compounds. In other words, the compound X may be contained in the non-aqueous electrolyte as an electrolyte salt, or may be contained as an additive (a component other than the electrolyte salt and the non-aqueous solvent).

[0087] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of non-aqueous solvents include cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. As the non-aqueous solvent, those in which some of the hydrogen atoms contained in these compounds are replaced with halogens may be used. Note that the unsaturated cyclic carbonate, which is compound X, does not fall under the category of non-aqueous solvents.

[0088] Examples of the cyclic carbonate include saturated cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), etc. Among these, EC and PC are preferred.

[0089] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among these, EMC is preferable.

[0090] As the non-aqueous solvent, it is preferable to use at least one of a cyclic carbonate and a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. By using a cyclic carbonate, it is possible to promote dissociation of the electrolyte salt and improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, it is possible to keep the viscosity of the non-aqueous electrolyte low. When a cyclic carbonate and a chain carbonate are used in combination, it is preferable that the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is, for example, in the range of 5:95 to 50:50.

[0091] The electrolyte salt can be appropriately selected from known electrolyte salts, and lithium salts are usually used as the electrolyte salt.

[0092] The lithium salt is LiPF 6 , LiBF 4 , LiClO 4 , LiN(SO 2 F) 2 Inorganic lithium salts such as LiN(SO 2 CF 3 ) 2 , LiN(SO 2 C 2 F 5 ) 2 , LiN(SO 2 CF 3 )(SO 2 C 4 F 9 Among these, inorganic lithium salts are preferred, and LiPF 6 is more preferred.

[0093] As described above, the salt having an anion having a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and not containing a nitrogen element, which is the compound X, and the salt having an oxalato complex anion can also be used as the electrolyte salt. One or more kinds of electrolyte salts can be used.

[0094] The electrolyte salt content in the non-aqueous electrolyte is 0.1 mol / dm at 20°C and 1 atmosphere. 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3 More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the nonaqueous electrolyte can be increased.

[0095] The non-aqueous electrolyte may contain other components in addition to the compound X, the non-aqueous solvent, and the electrolyte salt. Examples of the other components include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; succinic anhydride; Examples of the other components include glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride, dimethyl sulfite, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, diphenyl sulfide, thioanisole, diphenyl disulfide, dipyridinium disulfide, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, etc. These other components may be used alone or in combination of two or more.

[0096] The content of other components contained in the nonaqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of other components within the above ranges, it is possible to improve the capacity retention performance or cycle performance after high-temperature storage, and to further improve safety.

[0097] The nonaqueous electrolyte may be a combination of a nonaqueous electrolyte solution and a solid electrolyte. The solid electrolyte may be selected from any material that has lithium ion conductivity and is solid at room temperature (for example, 15°C to 25°C). Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and polymer solid electrolytes.

[0098] The shape of the nonaqueous electrolyte storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery, a flat battery, a coin battery, and a button battery.

[0099] Fig. 1 shows a nonaqueous electrolyte storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.

[0100] <Electricity storage device> The nonaqueous electrolyte storage element of the present embodiment can be mounted as an electricity storage unit (battery module) comprising a plurality of nonaqueous electrolyte storage elements assembled together in automobile power sources such as electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc., power sources for electronic devices such as personal computers and communication terminals, or power storage power sources, etc. In this case, the technology of the present invention may be applied to at least one of the nonaqueous electrolyte storage elements included in the electricity storage unit.

[0101] 2 shows an example of an electricity storage device 30 in which electricity storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte electricity storage elements 1, are further assembled. The electricity storage device 30 may include a bus bar (not shown) that electrically connects two or more nonaqueous electrolyte electricity storage elements 1, a bus bar (not shown) that electrically connects two or more electricity storage units 20, and the like. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more nonaqueous electrolyte electricity storage elements.

[0102] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> The method for producing the nonaqueous electrolyte storage element of the present embodiment can be appropriately selected from known methods. The method for producing the nonaqueous electrolyte storage element of the present embodiment includes, for example, preparing an electrode body, preparing a nonaqueous electrolyte, and housing the electrode body and the nonaqueous electrolyte in a container. The preparation of the electrode body includes preparing a positive electrode and a negative electrode, and forming the electrode body by stacking or rolling the positive electrode and the negative electrode with a separator interposed therebetween.

[0103] The method of housing the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the non-aqueous electrolyte solution may be injected through an injection port formed in the container, and then the injection port may be sealed.

[0104] <Other embodiments> The nonaqueous electrolyte storage element of the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.

[0105] In the above embodiment, the nonaqueous electrolyte storage element is used as a chargeable and dischargeable nonaqueous electrolyte secondary battery, but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The present invention can also be applied to various secondary batteries, electric double layer capacitors, lithium ion capacitors, and other capacitors.

[0106] In the above embodiment, the electrode assembly in which the positive electrode and the negative electrode are stacked with a separator interposed therebetween has been described, but the electrode assembly may not include a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state in which a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode. EXAMPLES

[0107] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0108] [Example 1] (Preparation of positive electrode) The positive electrode active material is LiMnO2 having an average primary particle size of 3.0 μm, an average particle size of 10.4 μm, and a ratio of the average particle size to the average primary particle size of 3.5. 2 O 4 (Spinel-type lithium manganese oxide A) was prepared. A positive electrode mixture paste was prepared containing the spinel-type lithium manganese oxide A, acetylene black (AB) as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder in a mass ratio (solid equivalent) of 95.5:3.0:1.5, and N-methylpyrrolidone (NMP) as a dispersion medium. This positive electrode mixture paste was applied to an aluminum foil as a positive electrode substrate and dried. Then, pressing was performed to obtain a positive electrode having a positive electrode active material layer.

[0109] (Preparation of negative electrode) A negative electrode mixture paste was prepared containing graphite as a negative electrode active material, styrene-butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener in a mass ratio (solid content equivalent) of 97.8:1.0:1.2, with water as a dispersion medium. This negative electrode mixture paste was applied to copper foil as a negative electrode substrate and dried. After that, pressing was performed to obtain a negative electrode having a negative electrode active material layer.

[0110] (Preparation of non-aqueous electrolyte) A non-aqueous solvent was mixed with ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 30:70, and LiPF was added as an electrolyte salt. 6 to 0.9 mol / dm 3 and lithium bis(oxalato)borate (LiBOB) at 0.1 mol / dm 3 A non-aqueous electrolyte was prepared by dissolving LiBOB in an amount of 1.6 mass %. Note that LiBOB corresponds to compound X, and the content of LiBOB in the non-aqueous electrolyte was 1.6 mass %.

[0111] (Preparation of separator) A polyolefin microporous film was prepared as a separator.

[0112] (Preparation of non-aqueous electrolyte storage element) The positive electrode and the negative electrode were laminated with the separator interposed therebetween to prepare an electrode assembly, which was then housed in a container made of a metal resin composite film, and the nonaqueous electrolyte was poured into the container, which was then sealed by thermal welding to obtain the nonaqueous electrolyte storage element of Example 1.

[0113] [Comparative Examples 1 to 3] Each of the nonaqueous electrolyte storage elements of Comparative Examples 1 to 3 was obtained in the same manner as in Example 1, except that the type of spinel-type lithium manganese oxide and the type and content of the electrolyte salt were as shown in Table 1. In Table 1, "-" indicates that the corresponding electrolyte salt was not contained.

[0114] In the following tables, the spinel-type lithium manganese oxide B has an average primary particle size of 1.5 μm, an average particle size of 17.7 μm, and a ratio of the average particle size to the average primary particle size of 11.8. 2 O 4 Shows.

[0115] [Example 2] (Preparation of positive electrode) A positive electrode mixture paste was prepared containing the spinel-type lithium manganese oxide A, acetylene black (AB) as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder in a mass ratio (solid equivalent) of 95.5:3.0:1.5, and N-methylpyrrolidone (NMP) as a dispersion medium. This positive electrode mixture paste was applied to an aluminum foil as a positive electrode substrate and dried. Then, pressing was performed to obtain a positive electrode having a positive electrode active material layer.

[0116] (Preparation of negative electrode) A negative electrode mixture paste was prepared containing graphite as a negative electrode active material, styrene-butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener in a mass ratio (solid content equivalent) of 97.8:1.0:1.2, with water as a dispersion medium. This negative electrode mixture paste was applied to copper foil as a negative electrode substrate and dried. After that, pressing was performed to obtain a negative electrode having a negative electrode active material layer.

[0117] (Preparation of non-aqueous electrolyte) A non-aqueous solvent was prepared by mixing ethylene carbonate (EC), propylene carbonate (PC), and ethyl methyl carbonate (EMC) in a volume ratio of 25:5:70, and LiPF was added as an electrolyte salt. 6 to 1.0 mol / dm 3 In the resulting solution, additives such as vinylene carbonate (X1) in a content of 0.4 mass%, lithium difluorophosphate (X2) in a content of 0.5 mass%, and 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane) (X3) in a content of 1.2 mass% were further dissolved to prepare a non-aqueous electrolyte.

[0118] (Preparation of separator) A polyolefin microporous film was prepared as a separator.

[0119] (Preparation of non-aqueous electrolyte storage element) The positive electrode and the negative electrode were laminated with the separator interposed therebetween to produce an electrode assembly, which was then housed in a container and the nonaqueous electrolyte was poured thereinto, followed by sealing to obtain a nonaqueous electrolyte storage element of Example 2.

[0120] [Example 3, Comparative Examples 4 and 5, Reference Examples 1 to 6] The nonaqueous electrolyte storage elements of Example 3, Comparative Examples 4 and 5, and Reference Examples 1 to 6 were obtained in the same manner as in Example 2, except that the type of spinel-type lithium manganese oxide and the type and content of additives were as shown in Tables 2 and 3. In Table 3, "-" indicates that the corresponding additive was not contained. The additives in Tables 2 and 3 are the following compounds. Each of the compounds X1 to X4 corresponds to compound X. X1: Vinylene carbonate X2: Lithium difluorophosphate X3: 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane) X4: Lithium bis(oxalato)borate Y1: Lithium difluorophosphonyl fluorosulfonylimide

[0121] [evaluation] (1)Initial charge / discharge The obtained nonaqueous electrolyte storage element was initially charged and discharged under the following conditions. In a thermostatic chamber at 25°C, constant current charging was performed with a charging current of 1.0C and a charge cut-off voltage of 4.10V, and then constant voltage charging was performed at 4.10V. The charge was terminated when the current attenuated to 0.01C. A rest period of 10 minutes was then provided. Constant current discharging was performed with a discharge current of 1.0C and a discharge cut-off voltage of 2.75V. A rest period of 10 minutes was then provided. The above charge and discharge were repeated twice, and the amount of electricity discharged in the second time was taken as the initial discharge capacity.

[0122] (2) Measurement of the recovery capacity retention rate after storage in a high-temperature environment Next, each of the nonaqueous electrolyte storage elements of Examples 1 to 3 and Comparative Examples 1 to 5 was charged at a constant current of 1.0C in a thermostatic chamber at 25°C to set the SOC to 50%. The SOC of 50% was calculated as half of the initial discharge capacity obtained in the above-mentioned "initial charge and discharge". In this SOC of 50%, each nonaqueous electrolyte storage element was stored in a thermostatic chamber at 65°C for 15 days. Then, the element was stored in a thermostatic chamber at 25°C for 3 hours. Then, the element was discharged at a constant current of 1.0C with a discharge cutoff voltage of 2.75V. Then, a rest period of 10 minutes was provided. Then, the discharge capacity after storage was determined in the same manner as in the above-mentioned "initial charge and discharge". The percentage of the discharge capacity after storage relative to the initial discharge capacity was determined as the recovery capacity maintenance rate after storage. The results are shown in Tables 1 and 2. In addition, each of the nonaqueous electrolyte storage elements of Reference Examples 1 to 6 was charged at a constant current of 1.0C in a thermostatic chamber at 25°C to a SOC of 50%. Each nonaqueous electrolyte storage element was stored in a thermostatic chamber at 45°C for 90 days in this SOC 50% state. Then, it was stored in a thermostatic chamber at 25°C for 3 hours. Then, it was discharged at a constant current of 1.0C with a discharge cut-off voltage of 2.75V. Then, a rest period of 10 minutes was provided. Then, the discharge capacity after storage was obtained in the same manner as in the above "initial charge and discharge". The percentage of the discharge capacity after storage relative to the initial discharge capacity was obtained as the recovery capacity maintenance rate after storage. The results are shown in Table 3.

[0123] [Table 1]

[0124] [Table 2]

[0125] [Table 3]

[0126] As shown in Table 1, the nonaqueous electrolyte storage element of Example 1, in which the ratio of the average particle diameter to the average primary particle diameter of the spinel-type lithium manganese oxide is 5 or less and the nonaqueous electrolyte contains LiBOB (lithium bis(oxalate)borate) as the compound X, has a higher recovered capacity retention rate after storage than the nonaqueous electrolyte storage elements of Comparative Examples 1 to 3 in which the ratio of the average particle diameter to the average primary particle diameter of the spinel-type lithium manganese oxide is not 5 or less or the nonaqueous electrolyte does not contain the compound X. Similarly, Examples 2 and 3 in Table 2 also have a high recovered capacity retention rate after storage. In addition, a comparison between Example 2 and Example 3 shows that the recovered capacity retention rate after storage is higher when the content of the compound X, vinylene carbonate (X1), is increased, and the effect of improving the recovered capacity retention rate after storage by vinylene carbonate (X1) was confirmed.

[0127] Table 3 shows, as a reference example, that each compound X is a component that can increase the recovery capacity retention rate after storage. Comparing Reference Example 1 with Reference Example 2, similarly to Example 1, the improving effect of lithium bis(oxalato)borate (X4) on the recovered capacity retention rate after storage was confirmed. In Reference Example 3, the content of lithium difluorophosphate (X2) was increased compared to Reference Example 1, and the recovered capacity retention rate after storage was increased. From this result, the improving effect of lithium difluorophosphate (X2) on the recovered capacity retention rate after storage was confirmed. Comparison between Reference Example 3 and Reference Example 4 confirmed the effect of 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane) (X3) in improving the recovered capacity retention rate after storage. On the other hand, a comparison between Reference Example 5 and Reference Example 6 showed that in the case of lithium difluorophosphonyl fluorosulfonylimide (Y1), which does not correspond to compound X, the recovered capacity retention rate after storage was reduced. From the above results, it is found that at least one compound X selected from the group consisting of a salt having an anion having a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and not containing a nitrogen element, a salt having an oxalato complex anion, an unsaturated cyclic carbonate, and a cyclic compound having a double bond between a sulfur atom and an oxygen atom is a component that can increase the recovered capacity retention rate after storage. It is also found that when such a compound X is contained in a non-aqueous electrolyte and a spinel-type lithium manganese oxide having a ratio of the average particle size to the average primary particle size of 5 or less is used in the positive electrode, the recovered capacity retention rate after storage in a high-temperature environment is further increased. [Industrial Applicability]

[0128] The present invention can be applied to nonaqueous electrolyte storage elements used as power sources for electronic devices such as personal computers and communication terminals, automobiles, industrial devices, and the like. [Explanation of symbols]

[0129] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. A positive electrode having a spinel crystal structure and containing a lithium transition metal oxide containing elemental manganese; Non-aqueous electrolyte Equipped with the lithium transition metal oxide is in the form of particles having a ratio of an average particle size to an average primary particle size of 5 or less; The nonaqueous electrolyte storage element includes at least one compound selected from the group consisting of a salt having an anion having a double bond between a sulfur atom or a phosphorus atom and an oxygen atom and not containing a nitrogen element, a salt having an oxalato complex anion, an unsaturated cyclic carbonate, and a cyclic compound having a double bond between a sulfur atom and an oxygen atom.

2. 2. The nonaqueous electrolyte storage element according to claim 1, wherein the compound is at least one selected from the group consisting of lithium difluorophosphate, lithium bis(oxalato)borate, vinylene carbonate, and 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane).

3. 3. The nonaqueous electrolyte storage element according to claim 1, wherein the content of the compound in the nonaqueous electrolyte is from 0.1% by mass to 10% by mass.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2012009270A

Cited By

  • Non-aqueous electrolyte and non-aqueous electrolyte secondary battery

    WO2026197154A1